Nexus Between Business Incubators, Commercializationand Innovation: Does Absorptive Capacity Act as a Mediator? (Journal of Asian Development Studies, 2026)
This paper examines the impact of business incubators on commercialisation and innovation among startupsin Pakistan, with particular attention to the mediating role of absorptive capacity. Based on the Resource-Based View, the research examines the potential of incubator-provided services to increase a firm’s capacity to acquire, assimilate, transform, and exploit knowledge to maximise innovation and commercial performance. A quantitative research design was utilised, and 141 respondents completed a structured questionnaire. Data were collected from 51 public and private incubators. To test the proposed relationships, statistical analyses, including descriptive statistics, Pearson correlation, confirmatory factor analysis, and structural equation modelling, were conducted. The findings show that business incubators positively affect both absorptive capacity and commercialisation and innovation. Although the absorptive capacity has a positive relationship with commercialisation and innovation, it did not support its mediating role in the structural model. These results indicate that incubators have a strong direct effect on the startup market and innovation performance, and the conversion of improved absorptive capacity into quantifiable commercialisation performance may require supplementary organisational or contextual environments. The research paper adds to the scant empirical evidence on incubation in developing economies and offers practical implications for incubator managers and policymakers seeking to enhance startup support systems. It is recommended that future studies adopt longitudinal designs and investigate additional mediators to understand the mechanisms underlying the production of knowledge-based performance gains.